Can the Concept of Lifestyle Migration be applied to Return Migration? The Case of Estonians in the UK. (13th June 2019) - Saar, Maarja; Saar, Ellu
Abstract: This article makes the case for using the concept of lifestyle migration to understand return migration. The key argument is that there are several advantages for engaging with lifestyle migration literature when analysing people's return, of which the prime reason is to draw attention away from the affective and emotional aspects of return migration and view it as a conscious decision related to future planning. A combination of statistical data and interviews with highly skilled Estonian migrants in the UK shows how the return of these migrants is often related to moving from one life stage to another. In the conscious process of planning for a family, several aspects related to both countries were evaluated and the return was often explained as benefitting the (potential) family. The article also claims that there is a need for lifestyle migration research to engage more actively on interlinkages between lifestyle and life stage.